2013
DOI: 10.1088/1612-2011/10/9/095901
|View full text |Cite
|
Sign up to set email alerts
|

Effects of laser-induced quenching and restoration of photoluminescence in hybrid Si/SiOxnanoparticles

Abstract: We studied the processes of pulsed and continuous-wave (CW) laser excitation of photoluminescence (PL) in nc-Si/SiOx nanoparticles. CW laser irradiation of the nc-Si/SiOx sol in dimethylsulfoxide (DMSO) and in a thin film was found to quench PL with an essentially nonexponential dynamics. The laser-induced variation of the Rayleigh scattering signal from the nc-Si/SiOx sol in DMSO was found to replicate that of the PL quenching. The IR and Raman spectra of the laser-exposed nc-Si/SiOx exhibited no new bands t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
13
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 22 publications
1
13
0
Order By: Relevance
“…In the course of such synthesis, a microdispersed powder of silicon monoxide, having an average particle size of *100 nm, turns into a sol of Si/ SiO x -NP, possessing a stable, intense red-infrared photoluminescence. It was found that the characteristic feature of the red-infrared PL of Si/SiO x nanoparticles is the sensitivity of PL parameters to the external environment and intense laser irradiation [7,8]. Notice that the non-photoluminescent Si-NP was obtained by a similar method in [21].…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…In the course of such synthesis, a microdispersed powder of silicon monoxide, having an average particle size of *100 nm, turns into a sol of Si/ SiO x -NP, possessing a stable, intense red-infrared photoluminescence. It was found that the characteristic feature of the red-infrared PL of Si/SiO x nanoparticles is the sensitivity of PL parameters to the external environment and intense laser irradiation [7,8]. Notice that the non-photoluminescent Si-NP was obtained by a similar method in [21].…”
Section: Introductionmentioning
confidence: 97%
“…Of particular interest are quantum-dimensional silicon nanoparticles (Si-NP) with a core size of up to 5 nm, having a bright photoluminescence (PL) in the red and infrared area of the spectrum and the typical life times of 10-10 2 ls [3][4][5][6][7]. The origin of the red-infrared photoluminescence of Si/SiO x -NP is associated with the presence in such nanoparticle composition of silicon suboxide (SiO x ), which contains photoluminescent centers (npODC) related to oxygen deficiency [8]. Photoluminescence of npODC in such a core/shell nanoparticle (Si/SiO x ) is the result of radiative recombination of excitons localized in the nanocrystalline cores of the nanoparticles after photon absorption by crystalline core.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A general decrease of the absorbance level is observed, demonstrating the intrinsic instability of the lightassembled nanoparticles. This implies the reversibility of the NP production assisted by light, which can be speeded up by resonant light [6,7,21]. Moreover, during the spontaneous relaxation in the dark, the shape of the resonance band changes: the 730 nm peak decreases faster than the 830 nm one.…”
mentioning
confidence: 99%
“…Some of the promising directions of present-day nanosilicon-based nanophotonics and optoelectronics [1][2][3][4][5][6][7] require the formation of silicon quantum dots with an optically or electrically controllable photoluminescence properties. The photoluminescence of silicon quantum dots having a size less than the Bohr radius for free excitons (4.3 nm) is associated with the radiative recombination of charge carriers limited to the size of the silicon nanoparticle core [8,9].…”
Section: Introductionmentioning
confidence: 99%